The effectiveness of giving Android-based applications as promotional media in improving COVID-19 preventive behavior in the community - Ira Purnamasari; Ferry Effendy; Dede Nasrullah; Lailatun Ni’mah (Universitas Muhammadiyah Surabaya, 2023)
Public understanding of COVID-19 is the main focus to break the chain of spread. The massive spread of the virus shows the lack of public knowledge about preventing transmission. The best way to prevent and slow down transmission is to get information about COVID-19. There are still limited promotional media in providing health education in the community, especially Android-based applications. The purpose of this study was to determine the effect of giving an Android-based application as a promotional medium in improving COVID-19 prevention behavior in the community. This study used a pre-experimental research design with one group pre-test and post-test design. The population is all people in the Mulyorejo village amounted to 22.862 and taken samples of 193 people using a non-probability purposive sampling technique with the respondent criteria aged 31-45 years. The knowledge questionnaire consisted of 20 statements and the attitude questionnaire with 18 statements. The statistical test uses the Wilcoxon Signed Rank Test to find out differences in knowledge and uses the Chi-Square Test to find out differences in attitudes. The results of knowledge have increased from pre-test sufficient knowledge (52.8%) and post-test good knowledge (80.3%) using the Wilcoxon signed rank test p=0.000<0.05. The results of attitudes have increased from pre-test negative attitudes (63.2%) and post-test positive attitudes (76.2%) using the Chi-square test p=0.000<0.05. The conclusion is that there is an effect of giving Android-based applications as a promotional medium in improving COVID-19 prevention behavior in the community.